Optimalisasi Kesamaptaan Holistik untuk Kesiapan Fisik, Mental, dan Sosial dalam Seleksi dan Pelatihan Kedinasan untuk CPNS TNI dan Polri di Masyarakat Medan - Faiza, Nayla Nur; Sembiring, Zamalludin (Al-DYAS, 2025)
This study is motivated by the importance of holistic fitness—an integrated approach that includes physical, mental, and social readiness—in facing the selection and training process for civil service positions, particularly for prospective members of the TNI and Polri. The aim of this research is to examine efforts to optimize holistic fitness among the people of Medan as a strategy to enhance selection success rates and the effectiveness of official training programs. A descriptive qualitative method was used, with data collected through observation, interviews, and questionnaires distributed to prospective selection participants and physical and mental trainers. The findings show that physical readiness must be supported by mental resilience and social skills in order for participants to navigate each stage of the selection process effectively. Among the Medan community, levels of physical and mental readiness were reported as ready and very ready at 85%, while social readiness reached 90%. However, challenges remain, particularly the low awareness among some community members regarding the importance of comprehensive preparation as a prerequisite for success in the selection process. Therefore, a systematic and continuous holistic fitness development program is needed, involving educational institutions, community leaders, and relevant agencies. The conclusion of this study is that optimizing holistic fitness is a strategic step in preparing the Medan community to face the selection and training process for civil service roles more effectively.